2011
DOI: 10.2169/internalmedicine.50.5856
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase G894T Gene Polymorphism and Essential Hypertension in the Chinese Population: a Meta-Analysis Involving 11,248 Subjects

Abstract: Background The endothelial nitric oxide synthase (eNOS) G894T gene polymorphism has been suggested to be linked to the risk of essential hypertension (EH), however the results are still debatable. Objective and Methods To assess the association between eNOS G894T gene polymorphism and EH, such electronic databases as Pubmed, Embase, Web of Science, China Biological Medicine Database (CBMD) and China National Knowledge Infrastructure (CNKI) were searched. The selection criteria were as follows: a) Evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Genetic polymorphisms of the eNOS gene are good candidates for predicting the risk associated with cardiovascular diseases such as coronary artery disease, atrial fibrillation, and essential hypertension [ 26 28 ]. eNOS G894T is one of the most common variants of eNOS, the others being T-786C and 4b4a mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms of the eNOS gene are good candidates for predicting the risk associated with cardiovascular diseases such as coronary artery disease, atrial fibrillation, and essential hypertension [ 26 28 ]. eNOS G894T is one of the most common variants of eNOS, the others being T-786C and 4b4a mutations.…”
Section: Discussionmentioning
confidence: 99%
“…eNOS-derived NO plays an important role in the maintenance of vascular homeostasis, including regulation of the cerebral circulation [10]. Besides, previous studies suggested that eNOS gene (4b/a,T-786C,G894T) polymorphisms are significantly associated with hypertension [47], [48], total cholesterol and low-density lipoprotein cholesterol levels [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism allows the generation of two isoforms of endothelial NOS3: NOS3 Glu298 (allele G) and NOS3 Asp298 (allele T) [83]. It is a functional polymorphism, which influences the activity of the enzyme, NO production, blood pressure [17,84], lipid levels [85], and angiogenesis [86] with people with the T allele being particularly homozygous, associated with less enzyme activity [84] and the highest cardiovascular risk [18,19,85], reduced NO bioavailability engaging in the initiation, progression, and complications of atherosclerosis [87] less likely to achieve longevity [16]. These mechanisms can explain what was observed in the present study of the synergistic interaction of NOS3 genotypes with the degree of HT in longevity (Figures 2 and 3) as well as the potentially additive effect of smoking, hypercholesterolemia, obesity, and frequent consumption of red meat (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Other genes, such as angiotensinogen (AGT), specifically the AGT M235T polymorphism, may be associated with chronic age-associated CVDs [15]. As for NOS3, this is a determinant polymorphism for the production of nitric oxide, with consequent implications for the development of atherosclerosis, hypertension [16,17], and Alzheimer's, with impact on cardiovascular risk and longevity [16,[18][19][20]. Variants of the AT1 receptor of angiotensin II (AGTR1) [21] and other genetic polymorphisms such as the G protein-coupled receptor kinase 4 (GRK4) [22,23] and solute carrier family 12 member 3, SLC12A3 [24], have been related to arterial hypertension and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%